Screening of Industrially Important Enzymes Produced by Moderately Halophilic Bacteria Isolated from Salted Sheep Skins of Diverse Origin - (:unkn) unknown (AMER LEATHER CHEMISTS ASSOC, 2017)
Moderately halophilic bacteria have received attention in several industries due to their industrial enzymes which are stable at high temperatures, various salt concentrations and different pH values. Therefore, this study was conducted to isolate and identify moderately halophilic bacteria found on salted sheep skin samples and to detect the isolates producing industrially important enzymes. These skin samples were from Australia, Bulgaria, Dubai, Greece, Israel, Kuwait, South Africa, Turkey and U.S.A. Phenotypic characteristics and comparative partial 16S rRNA gene sequence analysis were used to characterize these microorganisms. According to the test results, 77 isolates representing 13 genera and 29 species were identified. These moderately halophilic bacteria, which were able to mostly grow in the media containing 3-15% salts and in some cases, up to 20-25% salts, were closely related to species of genera Staphylococcus, Salimicrobium, Bacillus, Salinicoccus, Planococcus, Alkalibacillus, Gracilibacillus, Oceanobacillus, Marinococcus, Halomonas, Salinivibrio, Chromohalobacter, and Idiomarina. A fairly high percentage of the isolates (79%) produced a great variety of industrially important enzymes. Protease, lipase, beta-galactosidase, amylase, caseinase,, DNase, urease, cellulase, and lecithinase enzymes were produced respectively by 46, 33, 30, 20, 18, 13, 9, 9, and 8 isolates. None of the isolates produced pullulanase, xylanase and phospholipase enzymes. Combined enzymatic activities have been detected among the isolates. While 12% and 27% of isolates produced six and four different enzymes, respectively, 1% of isolates produced three different enzymes. Furthermore, 39% of the isolates produced one and two enzymes. These enzymes were produced by isolates belonging to all genera detected in this study except genus Alkalibacillus. The findings of this study demonstrated that moderately halophilic bacteria on the skins produced industrially important enzymes which may have potential applications in different industries.